Wild-type Caenorhabditis sinica, a model nematode for speciation and evolution, massively found in Vietnam - Tho Son, Le; Hong Gam, Nguyen Thi; Thi Thu, Nguyen; Hong Loan, Do Thi (Vietnam Journal of Biotechnology, 2023)
Caenorhabditis sinica is a male/female species, in which the genetic diversity is possibly high. Thus, the species is advantageous for the understanding of the mechanisms of diversity, evolution, and adaptation within the nematode genus Caenorhabditis. Previous studies reported the geographic distribution of C. sinica only in China; nonetheless, this should be more convincing for its ecology. We allegedly surveyed the Caenorhabditis species and their diversity in the forests of Vietnam. We found 59 C. sinica strains, and this therefore indicates the vast variation that is 85.88% and 100% identical within isolated wild-type strains. They unequally present in habitats and are enormous in the northern forest, and rarer in the southern forest. The comparison of 18S rDNA barcode sequences from 59 C. sinica isolates by nucleotide sequence alignment showed the consistent diversity among the strains in or off the same ecologies, and all are comparable with the ever-first isolated strain JU727.